2020
DOI: 10.1007/s00404-020-05670-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated fibronectin as a first trimester marker for gestational diabetes

Abstract: Purpose To evaluate the performance of first trimester maternal serum glycosylated (Sambucus nigra lectin-reactive) fibronectin in prediction of gestational diabetes mellitus (GDM). Methods In this case-control study, first trimester maternal serum glycosylated fibronectin and fibronectin were measured in 19 women who consequently developed GDM and in 59 control women with normal pregnancy outcomes. Adiponectin was used as a reference protein to evaluate relation of glycoprotein to SNA-lectin-reactive assay fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…Elevated GlyFn was demonstrated in the first trimester in women who subsequently developed gestational diabetes 30,31 . However, a more recent study by Alanen et al 32 . reported no association between GlyFn level and gestational diabetes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Elevated GlyFn was demonstrated in the first trimester in women who subsequently developed gestational diabetes 30,31 . However, a more recent study by Alanen et al 32 . reported no association between GlyFn level and gestational diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Elevated GlyFn was demonstrated in the first trimester in women who subsequently developed gestational diabetes 30,31 . However, a more recent study by Alanen et al 32 reported no association between GlyFn level and gestational diabetes. It should be noted that the latter study included only 78 women, of whom 19 had gestational diabetes, and used a self-developed internal ELISA test, which may have targeted different glycosylation sites and used different monoclonal antibodies compared with the assays used in the present and prior studies.…”
Section: Implications For Clinical Practicementioning
confidence: 92%
“…The adverse effects of gestational diabetes mellitus are not limited to the pregnancy but can also have an impact on health both mothers and infants. 2 The adoption of the new diagnostic criteria based on the recent HAPO study is expected to increase the prevalence of gestational diabetes mellitus to approximately 18% of all pregnancies. About 5-10% of women with gestational diabetes mellitus are diagnosed with type 2 diabetes immediately after pregnancy, while the presence of obstetrical history of gestational diabetes mellitus is associated with a 10-fold higher chance of developing diabetes within the next 10-20 years.…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…Apparently, these criteria may lead to different diagnostic power indices (sensitivity, speci city, positive and negative predictive values, area under the ROC curve and so on) subject to the characteristics of the target population (11,20). In addition to the standard methods of screening, a number of studies evaluated the diagnostic accuracy of the rst or second-trimester maternal markers for early detection of GDM using different statistical techniques (21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the related published literature indicates that most of researchers have investigated the information from a single biomarker or multiple biomarkers in the rst or early second trimester of pregnancy for early detection of GDM. The beta-human chorionic gonadotropin (β-hCG), tumor-necrosis factor alpha (TNFα), unconjugated estriol (uE3), alfa-fetoprotein (AFP), pregnancy-associated plasma protein A (PAPP-A), soluble endoglin, placental protein 13 (PP13), adiponectin (Adipo), and a number of other adipose tissue-derived and placenta-related factors are among these biomarkers (21)(22)(23)(24)(25)(26). At the same time, a number of studies have focused on the available data from the more common indicators in complete blood count (CBC) tests for early prediction of GDM (27)(28).…”
Section: Introductionmentioning
confidence: 99%